Processing method of different-shrinkage imitated acetate fibers
Through the processing method of heteroshrinkage acetic acid wire, the problems of poor hygroscopicity and insufficient strength of acetate fibers and polyester fibers were solved, and fibers with excellent hygroscopicity, toughness and antistatic properties were prepared, which improved the wear comfort of the fabric.
Patent Information
- Application Number
- CN202411755530.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
AI Technical Summary
Existing acetate fibers and polyester fibers have poor hygroscopicity and insufficient strength in textiles, which affect the wear comfort of the fabric.
Using the processing method of heteroshrinkage acetic acid wire, a leather core structure and S-shaped groove are prepared by mixing the large light PET slice with antistatic agent and toughening agent, and through screw extrusion, spinning and elastic adding processes. Fiber, improves the hygroscopic, toughness and antistatic properties of the fiber.
The excellent moisture absorption and strength of the fiber is achieved, the moisture absorption and sweating performance of the fabric is improved, and the toughness and antistatic properties of the fiber are further improved through the synergistic effect of the antistatic agent and the toughening agent.
Smart Images

Figure CN119221142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber technology, and more specifically to a processing method of different shrinkage imitation acetate fibers. Background Art
[0002] Acetate fiber is made from cellulose acetate, a derivative of cellulose. Acetate fiber not only has the characteristics of cellulose fiber, but also exhibits good hygroscopicity and antistatic properties. The filaments are elegantly glossy, soft to the touch, and have good drape, similar to real silk. It is suitable for making underwear, bathrobes, children's clothing, interior decoration fabrics, clothing (especially high-end clothing) linings, satin fabrics and braids, fashion and high-end clothing fabrics. Although acetate fiber has many advantages, it has the disadvantages of being more expensive and having poor strength. Its wet antistatic property is even lower, which seriously affects its application and promotion in textiles.
[0003] Polyester fiber is the most produced variety among synthetic fibers today, and is widely used in clothing fabrics, home textiles and other fields. However, due to its special molecular structure, its hygroscopicity is relatively poor, which affects people's wearing comfort. If a modified polyester fiber with excellent hygroscopicity and strength can be developed to improve the wearing comfort of fabrics, it will have broad application prospects. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for processing shrinkage-imitation acetate fibers. The obtained fibers have excellent moisture absorption, toughness and antistatic properties, can effectively replace acetate fibers, and improve the wearing comfort of fabrics.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for processing different shrinkage imitation acetate silk comprises the following steps:
[0007] a. Evenly mix the crystallized and dried high-gloss PET slices with an antistatic agent accounting for 0-5% of the slice mass and a toughening agent accounting for 0-5% of the slice mass, and melt-extrude the mixture through a screw extruder to obtain a skin layer melt. Melt-extrude the crystallized and dried high-shrinkage PET slices through another screw extruder to obtain a core layer melt. The core layer melt and the skin layer melt are injected into a two-component composite spinning assembly for spinning to obtain a skin-core structured primary yarn.
[0008] b. The raw yarn is cooled by side blowing, oiled, and pre-networked, and then stretched and shaped by the first and second godet hot rollers, and then wound and formed to obtain POY yarn;
[0009] c. The POY yarn is introduced into the texturing machine. The yarn bundle passes through the raw yarn rack, and then passes through the first roller, the first heat box, the cooling plate, the false twister, the second roller, the second heat box, and the third roller in sequence, and then is networked, oiled, and wound to obtain a different-shrinkage imitation acetate yarn with a circular core layer cross-section and a polygonal star-shaped skin layer cross-section. The obtained imitation acetate yarn has S-shaped grooves on the outer wall of the skin layer and along the length direction of the polyester fiber.
[0010] Furthermore, the two-component composite spinning assembly includes a spinneret, and the cross-section of the discharge hole of the spinneret is a regular polygonal star.
[0011] Furthermore, the mass ratio of the imitation acetate silk core layer to the skin layer is 1-2.5:1.
[0012] Furthermore, the cortical cross-section of the imitation acetate silk is a polygonal star with 5 or more angles.
[0013] Furthermore, in step a, the glossy PET slices are crystallized at 155-165°C and dried at 150-160°C, and the moisture content of the glossy PET slices after treatment is 20-30 ppm; the high shrinkage PET slices are crystallized at 160-165°C and dried at 155-160°C, and the moisture content of the high shrinkage PET slices after treatment is 20-30 ppm.
[0014] Furthermore, in step a, when the high-gloss PET slices are mixed with an antistatic agent and a toughening agent to prepare the skin layer melt, the antistatic agent is the antistatic agent LUBDE 12B-P, and the toughening agent is the organosilicon toughening agent GENIOPERL P52.
[0015] Furthermore, in step a, when the bright PET chips are melt-extruded, the temperatures of zones 1 to 5 of the screw extruder are 270-280°C, 280-285°C, 285-290°C, 285-290°C, and 290-295°C, respectively; when the high-shrinkage PET chips are melt-extruded, the temperatures of zones 1 to 5 of the screw extruder are 260-270°C, 270-280°C, 280-285°C, 280-285°C, and 285-290°C, respectively.
[0016] Furthermore, in step a, the spinning temperature is 290-295° C., and the spinning pressure is 8-12 MPa.
[0017] Furthermore, in step b, the side blowing temperature is 20-25°C, and the wind pressure is 50Pa; the oiling rate is 0.5-0.9wt%; the pre-network pressure is 0.07-0.15MPa; the speed of the first wire guide hot roller is 2200-3200m / min, the speed of the second wire guide hot roller is 2210-3210m / min, the winding speed is 2200-3200m / min, and the winding tension is 10-11cN.
[0018] Furthermore, in step c, the speed of the first roller is 320-330 m / min; the temperature of the first hot box is 180-190°C; the D / Y ratio of the false twister is 1.5-1.7; the speed of the second roller is 560-580 m / min, and the temperature of the second hot box is 110-130°C; the speed of the third roller is 810-830 m / min; the oiling rate is 3-4wt%; the network pressure is 0.15-0.3 MPa; and the winding speed is 510-530 m / min.
[0019] The beneficial effects of the present invention are as follows: by designing a fiber cross-section with a circular core layer cross-section and a polygonal star cross-section in the skin layer, combined with improvements in spinning and texturing processes, an iso-shrinkage imitation acetate fiber with an S-shaped groove is prepared, the fiber has excellent moisture absorption performance and strength, and the moisture absorption and perspiration performance of the fabric is effectively improved; in particular, after adding an antistatic agent LUBDE12B-P and an organosilicon toughening agent GENIOPERL P52 to the fiber skin layer, it is found that the antistatic agent and the toughening agent have a synergistic effect, which further improves the toughness and antistatic performance of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a cross-sectional schematic diagram of the different shrinkage imitation acetate silk of the present invention;
[0021] Figure 2 It is a schematic diagram of the appearance of the different shrinkage imitation acetate silk of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The processing method of the different shrinkage imitation acetate silk of the present invention comprises the following steps:
[0024] a. Crystallize and dry conventional high-gloss PET slices and high-shrinkage PET slices (shrinkage rate ≥ 20%) respectively. The conventional high-gloss PET slices are crystallized at 155-165°C and dried at 150-160°C. The moisture content of the treated high-gloss PET slices is 20-30ppm; the high-shrinkage PET slices are crystallized at 160-165°C and dried at 155-160°C. The moisture content of the treated high-shrinkage PET slices is 20-30ppm; the crystallized and dried conventional high-gloss PET slices are mixed with an antistatic agent accounting for 0-5% of the slice weight (preferably the antistatic agent LUBDE 12B-P purchased from Shanghai Dirun Chemical Co., Ltd.) and a toughening agent accounting for 0-5% of the slice weight (preferably the silicone toughening agent GENIOPERL purchased from Nagase Group) P52, which is a powdered granular polymer modifier composed of a low modulus cross-linked silicone core and an organic polymer shell) was mixed evenly and melt-extruded through a screw extruder (the temperatures of the first to fifth zones of the screw extruder were 270-280°C, 280-285°C, 285-290°C, 285-290°C, and 290-295°C, respectively) to obtain a skin melt; the high shrinkage PET slices after crystallization and drying were melt-extruded through another screw extruder (screw extruder The temperatures of the first to fifth zones are 260-270°C, 270-280°C, 280-285°C, 280-285°C, and 285-290°C, respectively), to obtain a core layer melt; the core layer melt and the skin layer melt are injected into a two-component composite spinning assembly for spinning (the two-component composite spinning assembly includes a spinneret, and the cross-section of the discharge hole of the spinneret is a regular polygonal star; the spinning temperature is 290-295°C, and the spinning pressure is 8-12MPa), to obtain a skin-core structured primary yarn;
[0025] b. The raw yarn is cooled by side blowing, oiled, and pre-networked, and then stretched and shaped by the first and second godet hot rollers, and then wound and formed to obtain POY yarn;
[0026] Among them, the side blowing temperature is 20-25℃, the wind pressure is 50Pa; the oiling rate is 0.5-0.9wt%; the pre-network pressure is 0.07-0.15MPa; the speed of the first wire guide hot roller is 2200-3200m / min, the speed of the second wire guide hot roller is 2210-3210m / min, the winding speed is 2200-3200m / min, and the winding tension is 10-11cN.
[0027] c. The POY yarn is introduced into the texturing machine. After passing through the raw yarn rack, the yarn bundle passes through the first roller, the first heat box, the cooling plate, the false twister, the second roller, the second heat box, and the third roller in sequence, and then is networked, oiled, and wound to obtain a different shrinkage imitation acetate yarn with a circular core layer cross section and a polygonal star cross section. The obtained imitation acetate yarn has S-shaped grooves on the outer wall of the cortex and along the length direction of the polyester fiber. The schematic diagram of the fiber cross section is shown in FIG. Figure 1 , the fiber shape diagram is shown in Figure 2 The mass ratio of the core layer to the skin layer of the obtained imitation acetate silk cross section is 1-2.5:1; the skin layer cross section of the imitation acetate silk is preferably a polygonal star with 5 or more angles.
[0028] In step c, the speed of the first roller is 320-330 m / min; the temperature of the first hot box is 180-190°C; the D / Y ratio of the false twister is 1.5-1.7; the speed of the second roller is 560-580 m / min, and the temperature of the second hot box is 110-130°C; the speed of the third roller is 810-830 m / min; the oiling rate is 3-4wt%; the network pressure is 0.15-0.3 MPa; and the winding speed is 510-530 m / min.
[0029] The preferred embodiments are as follows:
[0030] Example 1
[0031] a. The conventional glossy PET slices (viscosity of 0.68d1 / g) were crystallized at 160°C and dried at 155°C. The moisture content of the treated glossy PET slices was 25ppm. The high shrinkage PET slices (viscosity of 0.72d1 / g, shrinkage of 26.4%) were crystallized at 165°C and dried at 160°C. The moisture content of the treated glossy PET slices was 25.1ppm. The crystallized and dried glossy PET slices were melt extruded by a screw extruder (the temperatures of the first to fifth zones of the screw extruder were 25.1ppm and 25.1ppm, respectively). The temperatures of the first to fifth zones of the screw extruder are 263°C, 270°C, 281°C, 285°C, and 287°C, respectively), to obtain a skin layer melt; the high shrinkage PET slices after crystallization and drying are melt-extruded through another screw extruder (the temperatures of the first to fifth zones of the screw extruder are 263°C, 270°C, 281°C, 285°C, and 287°C, respectively), to obtain a core layer melt; the core layer melt and the skin layer melt are injected together into a two-component composite spinning assembly (wherein the cross-section of the discharge hole of the spinneret is a regular seven-pointed star) for spinning (spinning temperature is 292°C, spinning pressure is 10.9MPa), to obtain a skin-core structured primary yarn.
[0032] b. The raw yarn is cooled by side blowing, oiled, and pre-networked, and then stretched and shaped by the first and second godet hot rollers, and then wound and formed to obtain POY yarn;
[0033] In step b, the side blowing temperature is 22°C and the wind pressure is 50Pa; the oiling rate is 0.9wt%; the pre-network pressure is 0.08MPa; the speed of the first wire guide hot roller is 2500m / min, the speed of the second wire guide hot roller is 2525m / min, the winding speed is 3071m / min, and the winding tension is 10.7cN.
[0034] c. The POY yarn is introduced into the texturing machine, and the yarn bundle passes through the first roller, the first heat box, the cooling plate, the false twister, the second roller, the second heat box, and the third roller in turn, and then is networked, oiled, and wound to obtain a different shrinkage imitation acetate yarn with a circular core layer cross section and a polygonal star-shaped skin layer cross section, and the obtained imitation acetate yarn has S-shaped grooves on the outer wall of the skin layer and along the length direction of the polyester fiber. The mass ratio of the core layer to the skin layer of the obtained imitation acetate yarn is 2:1.
[0035] In step c, the speed of the first roller is 323 m / min; the temperature of the first hot box is 181°C; the D / Y ratio of the false twister is 1.61; the speed of the second roller is 580 m / min, and the temperature of the second hot box is 110°C; the speed of the third roller is 825 m / min; the oiling rate is 3.5 wt%; the network pressure is 0.2 MPa; and the winding speed is 530 m / min.
[0036] Comparative Example 1
[0037] Conventional high-gloss PET chips (viscosity of 0.68 d1 / g) were crystallized at 160°C and dried at 155°C, and the moisture content of the treated high-gloss PET chips was 25 ppm; the crystallized and dried conventional high-gloss PET chips were melt-extruded through a screw extruder (the temperatures of the first to fifth zones of the screw extruder were 272°C, 280°C, 285°C, 288°C, and 291°C, respectively) to obtain a melt; the melt was injected into a spinning assembly (the cross-section of the spinneret discharge hole of the spinning assembly was the same as that in Example 1) for spinning (spinning temperature of 292°C, spinning pressure of 10.9 MPa), and primary silk with a seven-pointed star-shaped cross-section was obtained; and then fibers were prepared according to steps b and c of Example 1.
[0038] Example 2
[0039] The different shrinkage imitation acetate fibers were prepared according to the method of Example 1, except that: in step a, the conventional high-gloss PET chips after crystallization and drying were evenly mixed with 3.1% of the weight of the chips by weight of the antistatic agent LUBDE 12B-P and 4.4% of the weight of the chips by weight of the organosilicon toughening agent GENIOPERL P52, and then melt-extruded by a screw extruder to prepare a skin melt.
[0040] Example 3
[0041] The iso-shrinkage imitation acetate silk was prepared according to the method of Example 2, except that the antistatic agent LUBDE 12B-P was not added.
[0042] Example 4
[0043] The different shrinkage imitation acetate fibers were prepared according to the method of Example 2, except that the organosilicon toughening agent GENIOPERL P52 was not added.
[0044] The properties of the imitation acetate silk prepared in Examples 1 to 4 were tested, and the results are shown in Table 1. The vertical wicking height and drip diffusion time were tested in accordance with GB / T 21655.1-2023 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method", and the specific test methods are shown in "7 Sampling and sample preparation", "8.2 Drip diffusion time" and "8.4 Wicking height" of the standard. The breaking strength and elongation of the fiber were tested in accordance with GB / T 14344-2022 "Test method for tensile properties of chemical fiber filaments", and the specific test methods are shown in "6 General test rules" and "7 Test steps" of the standard. The boiling water shrinkage rate is tested in accordance with GB / T 6505-2017 "Test method for thermal shrinkage of chemical fiber filaments". For specific test methods, please refer to the "7.1.2 Single root method" section of the standard; the surface charge density test method refers to GB / T 12703.2-2021 "Test method for electrostatic properties of textiles Part 2: Manual friction method". For specific test methods, please refer to the "7 Preparation of specimens" and "8 Test steps" sections of the standard.
[0045] Table 1
[0046]
[0047] As shown in Table 1, the acetate-like silk prepared in the embodiment of the present invention has good moisture absorption and strength, and can effectively improve the moisture absorption and perspiration effect of the fabric. In addition, by comparing Example 2 with Example 1, Example 3, and Example 4, it is found that when the antistatic agent LUBDE 12B-P and the organosilicon toughening agent GENIOPERL P52 are added to the fiber, the antistatic agent and the toughening agent have a synergistic effect, which further improves the toughness and antistatic performance of the fiber.
[0048] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for processing different shrinkage imitation acetate silk, characterized in that: The following steps are involved: a. Evenly mix the crystallized and dried high-gloss PET slices with an antistatic agent accounting for 0-5% of the slice mass and a toughening agent accounting for 0-5% of the slice mass, and melt-extrude the mixture through a screw extruder to obtain a skin layer melt. Melt-extrude the crystallized and dried high-shrinkage PET slices through another screw extruder to obtain a core layer melt. The core layer melt and the skin layer melt are injected into a two-component composite spinning assembly for spinning to obtain a skin-core structured primary yarn. b. The raw yarn is cooled by side blowing, oiled, and pre-networked, and then stretched and shaped by the first and second godet hot rollers, and then wound and formed to obtain POY yarn; c. The POY yarn is introduced into the texturing machine. The yarn bundle passes through the raw yarn rack, and then passes through the first roller, the first heat box, the cooling plate, the false twister, the second roller, the second heat box, and the third roller in sequence, and then is networked, oiled, and wound to obtain a different-shrinkage imitation acetate yarn with a circular core layer cross-section and a polygonal star-shaped skin layer cross-section. The obtained imitation acetate yarn has S-shaped grooves on the outer wall of the skin layer and along the length direction of the polyester fiber.
2. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: The two-component composite spinning assembly comprises a spinneret, and the cross section of the discharge hole of the spinneret is in the shape of a regular polygonal star.
3. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: The mass ratio of the imitation acetate silk core layer to the skin layer is 1-2.5:
1.
4. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: The cortical cross-section of the imitation acetate silk is a polygonal star with 5 or more angles.
5. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step a, the glossy PET slices are crystallized at 155-165° C. and dried at 150-160° C., and the moisture content of the glossy PET slices after treatment is 20-30 ppm; the high shrinkage PET slices are crystallized at 160-165° C. and dried at 155-160° C., and the moisture content of the high shrinkage PET slices after treatment is 20-30 ppm.
6. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step a, when the high-gloss PET slices are mixed with an antistatic agent and a toughening agent to prepare a skin layer melt, the antistatic agent is an antistatic agent LUBDE 12B-P, and the toughening agent is an organic silicon toughening agent GENIOPERL P52.
7. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step a, when the bright PET slices are melt-extruded, the temperatures of zones 1 to 5 of the screw extruder are 270-280°C, 280-285°C, 285-290°C, 285-290°C, and 290-295°C, respectively; when the high-shrinkage PET slices are melt-extruded, the temperatures of zones 1 to 5 of the screw extruder are 260-270°C, 270-280°C, 280-285°C, 280-285°C, and 285-290°C, respectively.
8. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step a, the spinning temperature is 290-295° C. and the spinning pressure is 8-12 MPa.
9. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step b, the side blowing temperature is 20-25°C, and the wind pressure is 50Pa; the oiling rate is 0.5-0.9wt%; the pre-network pressure is 0.07-0.15MPa; the speed of the first wire guide hot roller is 2200-3200m / min, the speed of the second wire guide hot roller is 2210-3210m / min, the winding speed is 2200-3200m / min, and the winding tension is 10-11cN.
10. The method for processing the different shrinkage imitation acetate silk according to claim 1, characterized in that: In step c, the speed of the first roller is 320-330 m / min; the temperature of the first hot box is 180-190°C; the D / Y ratio of the false twister is 1.5-1.7; the speed of the second roller is 560-580 m / min, and the temperature of the second hot box is 110-130°C; the speed of the third roller is 810-830 m / min; the oiling rate is 3-4wt%; the network pressure is 0.15-0.3 MPa; and the winding speed is 510-530 m / min.
Citation Information
Patent Citations
Flame-retardant antistatic PET / PTT composite fiber
CN104846474A
Preparing method of SSY-FDY compound fiber
CN110106582A
Core-offset hollow composite fiber and preparation method and application thereof
CN111394829A
Antistatic sheath-core composite polyamide fiber and preparation method thereof
CN117845368A
Multi-groove profiled fiber and preparation method of fabric of multi-groove profiled fiber
CN118407153A
